Dual VHF Stratospheric–Tropospheric Radar Measurements in the Lower Atmosphere - Iain M. Reid; Rüdiger Rüster; Peter Czechowsky; Gerhard Schmidt (Remote Sensing)
Radar observations of tropospheric and lower-stratospheric winds and density-normalized momentum flux made in northern Germany with two 53.5 MHz VHF MST radars over a period of one week in August 1986 are presented. One MST radar was a permanent installation, the SOUSY VHF Harz radar, located in the Harz Mountains, and the other temporarily installed about 27 km away from the Harz. The latter radar, the SOUSY VHF Lindau radar, was operated with a limited number of antennas and much-reduced power, making it effectively a tropospheric radar. Unusually, this small radar was successfully operated in Doppler beam steering (DBS) mode to measure winds and density-normalized momentum fluxes after correcting for biases in the beam look directions resulting from its small antenna aperture. We compared the winds and density-normalized upward fluxes in horizontal momentum measured using these two radars. The mean winds show good agreement between the two radars and with winds from radiosondes launched from Essen and Hannover. Density-normalized zonal momentum fluxes are similar in form between the two radars, but do show an offset when calculated over the entire observational period. Because of the agreement in form, the zonal mean flow accelerations calculated from them are similar, and so these results are consistent between the radars even though the topography is quite different. Although the observations were made many years ago, the results we present here are still of interest, because comparisons of closely spaced wind profiling radar observations are still relatively rare, radar measurements of tropospheric and stratospheric momentum fluxes are sparse, and the successful operation of a very small DBS radar operating in the lower VHF band is of particular interest from a technical perspective.